Valorization of spent coffee grounds: Bioactive recovery, health benefits, and sustainable applications - Trần Văn, Cường; Nguyễn Thị Thoa; Nguyễn Đình Sỹ (Tay Nguyen Journal of Sciences, 2025)
Spent coffee grounds (SCGs), a major by-product of the coffee industry, are increasingly recognized for their rich profile of bioactive compounds and diverse functional properties. This review synthesizes current research on the chemical composition of SCGs, highlighting key constituents such as phenolic acids, flavonoids, dietary fiber, and melanoidins. Advanced extraction techniques, including supercritical CO₂ and ultrasound-assisted methods, have demonstrated effectiveness in maximizing the recovery of these bioactives. The health benefits of SCGs are evident in their strong antioxidant and anti-inflammatory activities, melanin inhibition relevant to cosmetic applications, and notable prebiotic potential that supports gut microbiota and short-chain fatty acid production. Beyond health, SCGs exhibit utility in industrial sectors, including food formulation, cosmeceuticals, pharmaceuticals, wastewater treatment, and environmental remediation. Emerging applications, such as enzyme immobilization and adsorbent material development for heavy metal removal, signal promising directions for future research. However, challenges such as regulatory approval, standardization, and consumer acceptance remain significant barriers to commercialization. This review concludes that valorizing SCGs represents a sustainable and economically viable strategy for circular bioeconomy models, and calls for further in vivo and clinical studies to validate their functional efficacy in human health and industrial settings.